Pelatihan Pengelolaan Media Sosial Bagi Muslim Milenial Dalam Meningkatkan Kecakapan Digital - Warsiyah; Hamam Burhanuddin; Ahmad Mujib (Politeknik Negeri Cilacap, 2023)
This service activity focuses on efforts to increase digital skills for millennial Muslim youth in managing social media which is a skill needed in the 21st century. The community service team from the Faculty of Islamic Religion, Sultan Agung Islamic University Semarang who facilitated the trainees, namely Muslim teenagers who were sitting at Madrasah Aliyah in Boyolali, Central Java. The service program uses a contextual approach, namely by linking the material presented with the needs and problems faced by millennial youth. Training activities begin with opening; continued identification and mapping of problems faced by millennial youth; assistance in the use of social media; evaluation and reflection on the results of the mentoring and the last is the closing. The results of this service program are able to increase the understanding of millennial Muslim youth regarding the functions and goals of social media, which is demonstrated by wiser attitudes and behavior in managing social media. Besides that, the digital skills of the trainees increased with indicators of positive content from their work being posted on social media.